Cultures, Citizenship and Human Rights - Buikema, Rosemarie; Buyse, Antoine; Robben, Antonius C.G.M (Routledge Advances in Sociology, 2019)
"In Cultures, Citizenship and Human Rights the combined analytical efforts of the fields of human rights law, conflict studies, anthropology, history, media studies, gender studies, and critical race and postcolonial studies raise a comprehensive understanding of the discursive and visual mediation of migration and manifestations of belonging and citizenship. More insight into the convergence, but also the tensions between the cultural and the legal foundations of citizenship, has proven to be vital to the understanding of societies past and present, especially to assess processes of inclusion and exclusion. Citizenship is more than a collection of rights and privileges held by the individual members of a state, but involves cultural and historical interpretations, legal contestation and regulation as well as an active engagement with national, regional and local state and other institutions about the boundaries of those (implicitly gendered and raced) rights and privileges. Highlighting and assessing the transformations of what citizenship entails today is crucially important to the future of Europe, which both as an idea and as a practical project faces challenges that range from the crisis of legitimacy to the problems posed by mass migration. Many of the issues addressed in this book however also play out in other parts of the world, as several of the chapters reflect. "